Cartera vencida en la empresa Bell Novainser S.A del cantón Babahoyo durante el periodo 2021 – 2022. - Mosquera Carpio, Belky Solange (2023)
The overdue portfolio refers to those credits or loans that a client or borrower has not paid within the agreed period. Therefore, the present investigation carried out in the Bell Novainser company of the Babahoyo Canton seeks to examine the overdue portfolio of the company during the period 2021 - 2022, to identify how it affects the liquidity of the company. For which the application of the Financial, Administrative, Tax, Audit and Control Management line of research was fundamental, which is based on recognizing that the problem of overdue loans in the company, and, in addition, the research subline " Audit and Control" since it plays an important role in the study of the overdue portfolio, because it will allow an in-depth analysis of the causes and factors that have contributed to the increase in the overdue portfolio in said period. Furthermore, it is essential to note that in this research it was chosen to use the deductive research approach, where, in addition, a descriptive methodology was used. This approach involved a detailed and systematic analysis of existing data on nonperforming loans, seeking to identify specific patterns, frequencies, and characteristics.